Relationship as an aspect of psychological climate of women's soccer team - Huzar, V. N.; Shalar, O. G.; Norik, A. O. (Physical Education of Students, 2014)
Purpose: to determine the level of psychological climate of women's soccer team. Studied levels of interpersonal relationships in women's football team. Material: in the study, which lasted 2 years, 14 football players participated Kherson female football club "Crystal". Results: It was determined that the team is dominated by emotional (0.6) and cognitive components (0.5). Girls come to know and understand each other, training takes place on a good emotional background. Observations and indicators of behavioral component (0.35), found that football players often do not yield to their teammates in stressful situations. Sometimes this leads to conflict situations. Conclusions: recommend indicators of relationships in women's soccer team coaches of team sports in building healthy psychological atmosphere.